Box-bhenken Design Combined with 3D Surface Methodology for Optimization of an Eco-friendly HPLC Method to Determine Venetoclax in Human Plasma, and its Bioanalytical Method Validation According to ICH M10 Guideline - Özcan, Saniye; Elriş, Abeer; Altun, Mazlum Akif; Levent, Serkan; Can, Nafiz Öncü (Current Analytical Chemistry, 2024)
<span class=
Keywords: HPLC